Challenges in Phosphorus Removal from Eutrophic Waters Using Adsorption: A Laboratory Comparison of Commercial and Moringa-Derived Adsorbents - Daniela Resende Duque; Adriano Gonçalves dos Reis; Jorge Kennety Silva Formiga; Suzelei Rodgher (Limnological Review, 2025)
To reduce the concentration of phosphorus, the main nutrient responsible for eutrophication, two adsorbents were tested: a commercial activated carbon and one produced from the pods of Moringa oleifera. A concentrated phosphorus solution representative of eutrophic ecosystems was produced at 0.210 mg·L−1 and used as the adsorbate. Thirty-nine laboratory samples were prepared with adsorbent dosages ranging from 0.5 g∙L−1 to 2.0 g∙L−1, and statistical analyses were applied to evaluate the results. An increase in the concentration of phosphorus in the solution was detected in all the tests. Desorption occurred due to the presence of nutrients in the composition of the adsorbents, in addition to the mild physical activation and the use of H3PO4 as a chemical activator of the natural adsorbent, which further favored desorption at equilibrium, even for activated carbon. This work, therefore, highlights the limitations of using the adsorption technique to remove phosphorus from eutrophic aquatic ecosystems. It is recommended that other activation methods for M. oleifera pods be studied for phosphorus removal from water, as well as adsorption equilibrium, kinetics, and thermodynamic studies.